Speckle variance optical coherence tomography of blood flow in the beating mouse embryonic heart - Grishina, Olga A. (J Biophotonics, 2017)
Efficient separation of blood and cardiac wall in the beating embryonic heart is essential and critical for experiment-based computational modelling and analysis of early-stage cardiac biomechanics. Although speckle variance optical coherence tomography (SV-OCT) relying on calculation of intensity variance over consecutively acquired frames is a powerful approach for segmentation of fluid flow from static tissue, application of this method in the beating embryonic heart remains challenging because moving structures generate SV signal indistinguishable from the blood. Here, we demonstrate a modified four-dimensional SV-OCT approach that effectively separates the blood flow from the dynamic heart wall in the beating mouse embryonic heart. The method takes advantage of the periodic motion of the cardiac wall and is based on calculation of the SV signal over the frames corresponding to the same phase of the heartbeat cycle. Through comparison with Doppler OCT imaging, we validate this speckle-based approach and show advantages in its insensitiveness to the flow direction and velocity as well as reduced influence from the heart wall movement. This approach has a potential in variety of applications relying on visualization and segmentation of blood flow in periodically moving structures, such as mechanical simulation studies and finite element modelling. [Figure: see text]